Studying on Vocal Music Teaching of Music Education Major in Sanmenxia Polytechnic in Sanmenxia City of Henan Province - Yu, Zhang; Banchongsilpa, Orawan (Journal of Roi Kaensarn Academi, 2024)
The purposes of these studies were to study vocal music teaching of music education major in Sanmenxia Polytechnic, Sanmenxia City, Henan Province.The researchers adopted qualitative research methods. The present situation of vocal music teaching in Sanmenxia Vocational and Technical College of Sanmenxia City, Henan Province is analyzed through investigation and interview. The aim of this study is to improve the teaching quality of vocal music course and train the educational talents to meet the needs of today's society. The research findings it is very important to balance theoretical knowledge and practical skills. In chapter one , the researcher briefly introduced the current situation of vocal music both at home and abroad. In chapter two, the researcher presents the related research and study. In chapter three, the researcher shares the structure and plan of the whole study. In chapter four, the researcher analyzes the data both the interview and the observation and finds that three professors have rich teaching experience and have their own understanding of the points the researcher focused on. They both agreed that even the current teaching situation in Sanmenxia Polytechnic is comparatively well, but music education major needs a broad and rich practice link to promote students' all-round development and improve their innovative ability, but in reality, practice link is usually insufficient, it is difficult to meet students' professional needs and practical ability training. In the true class, there are many problems existing, like the outdated textbooks, lack of the stage perform opportunities, need of of the diversified teaching method and so on. So in chapter five, the researcher proposes many suggestions based on the study from the theoretical prospect to the practical prospect, aiming to offer some help for vocal music teaching in Sanmenxia polytechnic